Evaluación de parámetros poblacionales y regeneración natural de Anadenanthera colubrina (Vell.) Brenan, en el valle de Vilcabamba, cantón Loja, Ecuador - Barrera Jiménez, Estefanía del Rocío (2023)
Studies on the dynamics of species populations are fundamental to understand their ecology. Anadenanthera colubrina (Vell.) Brenan is a native species of dry montane forests that is ecologically and economically important, as it has potential for restoration and sustainable forest management, but its populations are affected by habitat alteration. The objective of this research was to evaluate the spatial distribution, population density, age structure and natural regeneration of Anadenanthera colubrina (Vell.) Brenan, in the Vilcabamba valley. Systematic sampling was carried out by establishing 18 temporary plots of 20 x 20 m with a separation of 150 m between them, where individuals greater than 10 cm of D1.30 m and total height, geographic coordinates and phytosanitary status were recorded; to collect information on natural regeneration, subplots of 2 x 2 m were installed for seedlings and saplings, 5 x 5 m for low grassland and 10 x 10 m for high grasslandTo determine the spatial distribution we used the Standardized Morisita Index (Ip) and Nearest Neighbor Analysis in QGIS; the population density was determined with the absolute density equation; for the age structure we grouped the individuals in diameter classes; and for the regeneration evaluation we calculated the population mean growth in diameter and height and the structural parameters density, frequency and importance value index. The species shows a clustered spatial distribution pattern, the density is 239 ind/ha, the age structure shows a growing population with a greater number of juveniles. Natural regeneration is good, with saplings being the category with the highest number of individuals 119 ind/ha and also the one with the highest Importance Value Index. It was determined that the population and natural regeneration of Anadenanthera colubrina (Vell.) Brenan is high, which indicates that the species grows and has adequate ecological, environmental and topographic conditions for its development and therefore its populations are not affected. It is concluded that knowledge of the density and population structure of the species gives guidelines on its ecological requirements, provides information on its future persistence and suggests alternatives for its management and conservation. Key words: Anadenanthera colubrina, population dynamics, ecology, natural regeneration.